Seminal fluid and reproduction: much more than previously thought - Bromfield, John J. (Springer US, 2014)
The influence of seminal plasma on the cytokine and immune uterine environment is well characterised in mice and humans, while the effects of disruption to uterine seminal plasma exposure on pregnancy and offspring health is becoming more clearly understood. The cellular and molecular environment of the uterus during the pre- and peri-implantation period of early pregnancy is critical for implantation success and optimal foetal and placental development. Perturbations to this environment not only have consequences for the success of pregnancy and neonatal health and viability, but can also drive adverse health outcomes in the offspring after birth, particularly the development of metabolic disorders such as obesity, hypertension and insulin resistance. It is now reported that an absence of seminal plasma at conception in mice promotes increased fat accumulation, altered metabolism and hypertension in offspring. The evidence reviewed here demonstrates that seminal plasma is not simply a transport medium for sperm, but acts also as a key regulator of the female tract environment providing optimal support for the developing embryo and benefiting future health of offspring.